Configurational behavior and conductance of alkanedithiol molecular wires from accelerated dynamics simulations - Paz, Sergio Alexis (2012)
An accelerated dynamics scheme is employed to sample the configurational space of a system consisting of an alkanedithiol molecule confined to the gap between a metal tip and a perfect metal surface. With this information and by means of nonequilibrium green functions techniques (NEGF), conductance calculations are performed. The present results show that even for this system, which is one of the most simple conceivable because of the perfectness of the surface, a complex behavior appears due to the occurrence of an unexpected tip-molecule-surface arrangement, where the insertion of one of the molecular ends into the tip-surface gap generates configurations with strongly enhanced conductance. Estimates are also made for the time required to generate the molecular junction, indicating that it should depend on the tip-surface distance, thus opening the way to new experiments in this direction. © 2012 American Chemical Society.